The Moving Trajectory Fitting Based on Three-Dimensional Digital Model of Barchan Dunes in Taklimakan Desert - Aimin Lia; Zhiwen Han (Open Journal of Environmental Biology - Peertechz Publications, 2021)
In the hinterlands of the Taklimakan Desert, we monitored Barchan dune evolution with the Huace X90 GNSS in RTK working mode to obtain 3D coordinates of a dune with millimeter precision. Using these coordinates, a 3D digital model of the dune was built and superimposed with CASS 9.0 and ArcGIS 10.0. Auto CAD 2010 was used to draw an arc with the three elements of starting point, end point and included angle and to fit the corresponding characteristic point trajectory curve of the eight selected typical dunes. Results of the fitting showed that the dunes rotated counterclockwise with ranges of 33°∼38°and 25.5°∼30° in the monitoring intervals between stages one and two and stages three and four, respectively. The moving trajectories were curves pointing from NE to SW and convex to NW, with long lengths. Between stages two and three, the dunes rotated clockwise with a range of 31°∼37°, and the trajectories was curves pointing from NE to SW and convex to SE or SW, with varying direction and a short length. When the northward or southward angle between effective sand-driving wind and the axial direction was larger than 30°, the dune rotated clockwise or counterclockwise, respectively. This indicates that the moving trajectory should be a curve rather than a straight line, which would result in a better fit with the actual movement of the dune. Accurately fitting the moving trajectory of Barchan dunes can assist in learning how to fit the movement of other mobile dunes as well as how to correct raw dune evolution data, such as moving distance and speed. It can also lay a foundation for the improvement of a formula for moving speed, which is important because many fields of research concern the moving speed and direction of mobile dunes.